Redirecting an Anticancer to an Antibacterial Hit Against Methicillin-Resistant Staphylococcus aureus - Jang, Hye-Jeong; Chung, In-Young; Lim, Changjin; Chung, Sungkyun; Kim, Bi-o; Kim, Eun Sook; Kim, Seok-Ho; Cho, You-Hee (Frontiers in Microbiology, 2019)
YM155 is a clinically evaluated anticancer with a fused naphthoquinone-imidazolium scaffold. We here demonstrated that based on the weak or cryptic antibacterial activity of YM155 against methicillin-resistant Staphylococcus aureus (MRSA) (MIC of 50 μg/ml), some congeneric compounds with short alkyl chains (e.g. c5 with a hexyl chain) at the N3 position of the scaffold displayed more potent antibacterial activity against MRSA (MIC of 3.13 μg/ml), which is in a clinically achievable range. Their antibacterial activity was evident against Gram-negative bacteria only in the presence of the outer membrane-permeabilizing agent, polymyxin B. The antibacterial efficacy of c5 was confirmed using the Drosophila systemic infection model. We also characterized five spontaneous c5-resistant MRSA mutants that carry mutations in the ubiE gene for quinone metabolism and respiratory electron transfer and subsequently exhibit reduced respiration activity. The antibacterial activity of c5 was compromised either by an antioxidant, N-acetylcysteine, or in anaerobic condition. These suggest that the antibacterial mechanism of c5 involves the generation of reactive oxygen species (ROS) presumably during respiratory electron transport. This study provides an insight into “drug redirecting” by chemical modification based on an ROS-generating pharmacophore.